Drug Therapy Problem Identification and Resolution by Clinical Pharmacists in a Family Medicine Residency Clinic - Danielle MacDonald; Hannah Chang; Yi Wei; Keri D. Hager (University of Minnesota Libraries Publishing, 2018)
Purpose: There are limited data to evaluate the impact of ambulatory clinical pharmacist recommendations on family medicine resident prescribing and monitoring of medications. The purpose of this study is to begin to gain insight in this area by answering the research question, "How many ambulatory clinical pharmacist recommendations for drug therapy problem (DTP) resolution are implemented on the day of a medication therapy management (MTM) visit in an outpatient family medicine residency clinic?" Methods: This is a retrospective chart review of face-to-face MTM encounters conducted by ambulatory clinical pharmacists (including pharmacist residents) from August 1, 2012 to June 30, 2015 at a family medicine residency clinic. Descriptive statistics were conducted to both quantify the number of DTPs identified and resolved on the day of the MTM visit as well as categorize the DTPs. Results: Based on the 728 MTM encounters analyzed, patients were an average of 53.6 years old and took 11.9 medications to treat 5.7 medical conditions. A total of 3057 DTPs were identified in the 728 encounters, of which 1303 were resolved the same day as the MTM visit. This resulted in an average of 4.2 DTPs identified and 2.0 resolved per visit per patient. The most common DTP category identified in this study was the need for additional drug therapy (41.6%). Conclusions: Approximately half of the ambulatory clinical pharmacist's DTP resolution recommendations were implemented the same day they were identified, which highlights the strength of team-based patient care and interprofessional collaboration in a residency teaching clinic.   Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties. Treatment of Human Subjects: IRB determined project was non-HSR   Type: Original Research